Issues of Forming Inventory Management System in Small Businesses - Viktorovna, Inna Babenko; Ivanovich, Pavel Pochechun (International Review of Management and Marketing, 2016)
An increase in the inventories efficient use gives a jump-start to the growth of small business economic efficiency. Application of the system approach to inventory management allows monitoring the whole process of material flow and minimize randomness of this process. The very system of inventory management should be understood as a system of material flow planning, control and regulation. Application of the system approach to inventory management allows carrying out goal and target decomposition at different levels of management. For the said purpose, the stages of forming inventory management system taking into account the whole cycle of enterprise material flow are represented in the article. Keywords: Inventory, functions of the inventory management JEL Classifications: G31, L2